2023
DOI: 10.1002/erv.2999
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators affecting treatment uptake behaviours for patients with eating disorders: A systematic review synthesising patient, caregiver and clinician perspectives

Abstract: ObjectiveA significant treatment gap exists between persons affected by eating disorders (ED), and those engaging with treatment services. This systematic review aims to provide a thorough understanding of the barriers and facilitators affecting eating disorder treatment engagement, including a synthesis of the perspectives of patients, caregivers and healthcare professionals.MethodThis systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 99 publications
(162 reference statements)
1
10
0
Order By: Relevance
“…While parents reported that treatment improved family dynamics and mental health symptoms, many believed that it could only help with short-term improvements and viewed relapse as likely over the longer term (perhaps due to including parents of adults with AN). Competence of clinicians was a further concern of parents, a result that is consistent with another review where carers rated negative treatment experiences (e.g., low confidence in clinician) as the greatest barrier to treatment uptake (Daugelat et al, 2023).…”
Section: Control/curesupporting
confidence: 77%
“…While parents reported that treatment improved family dynamics and mental health symptoms, many believed that it could only help with short-term improvements and viewed relapse as likely over the longer term (perhaps due to including parents of adults with AN). Competence of clinicians was a further concern of parents, a result that is consistent with another review where carers rated negative treatment experiences (e.g., low confidence in clinician) as the greatest barrier to treatment uptake (Daugelat et al, 2023).…”
Section: Control/curesupporting
confidence: 77%
“…This is particularly important as previous studies showed that students are more likely to refer a friend to a psychologist than themselves (Raviv et al, 2009). The finding that students prefer to be self-reliant presents an opportunity to empower students to use evidence-based resources independently (e.g., self-help materials) to enable them to make positive changes as a first step (Gulliver et al, 2010), followed up by a supportive network to promote and facilitate help-seeking (Daugelat et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A shift from increasing ED literacy and changing attitudes towards help-seeking to addressing the firm believe that help is not required (i.e., denial) is necessary to enhance help-seeking. Despite the challenges of uptake and engagement, digital interventions should be considered to address help-seeking barriers (Ali et al, 2022;Daugelat et al, 2023). Further, it may be beneficial to increase students' self-awareness and recognition of their own (and others') ED symptoms and their impact on valued life domains in order to instil a perceived need for treatment (Gulliver et al, 2010;.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations